The Role of Motivational Mediation in Improving the Performance of Transportation Sector Employees: The Dynamics of Training and Competency - Nathasya, Fara Ditha; Suharsono, Riyanto Setiawan; Sanosra, Abadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study is motivated by the importance of improving the quality of human resources in the transportation sector, particularly at PT Kereta Api Indonesia Daop XI Jember, as an effort to achieve optimal operational performance. This research adopts a quantitative approach, a numerical method employing the Partial Least Square (PLS) technique with WarpPLS 8.0 software. The group includes every worker of PT Kereta Api Indonesia. Daop XI Jember, with a sample of 283 respondents selected using probability sampling through proportional random. Information was gathered via surveys and examined utilizing tests for validity and reliability, along with structural model assessment. The findings suggest that both training and skill positively and significantly influence motivation, and that training, skill, and motivation together also positively and significantly impact employee performance. Nonetheless, skill does not greatly influence performance via motivation, indicating that competence directly influences performance without being mediated by motivation. The originality of this research is found in analyzing motivation as an intermediary factor. These results add to theoretical understanding in creating models for human resource performance and offer practical insights for managing human resources within the transportation industry.